The Urgent Imperative of Research on Global Peace and Harmony - Trivedi, Priyaranjan (International Journal of Advanced Research in Peace, Harmony and Education; Vol 9 No 1 (2024): International Journal of Advanced Research in Peace, Harmony and Education, 2024)
In an increasingly turbulent world characterized by geopolitical tensions, regional conflicts, and social upheaval, the pursuit of global peace and harmony is imperative. This paper explores the urgent need for research in this area, presenting a comprehensive analysis of the multifaceted challenges threatening stability, security, and the well-being of humanity. The complexities of global challenges, including geopolitical tensions, socioeconomic disparities, and environmental degradation, underscore the necessity for evidence-based research. The human cost of conflict, encompassing loss of lives, displacement, and psychological trauma, further emphasizes the urgency of addressing these issues. Recognizing the interconnectedness of global issues, such as globalization and transnational threats, highlights the need for collaborative efforts in promoting peace and harmony. The paper underscores the imperative for research on peace and harmony, focusing on its role in informing policy, promoting sustainable development goals, and cultivating a culture of peace. It explores strategies for advancing conflict prevention and resolution efforts, including early warning systems, mediation, and leveraging technology for peacebuilding. Strengthening international cooperation and partnerships, both within institutions like the United Nations and through civil society engagement, emerges as crucial in overcoming challenges to peace. Ethical considerations in peace research, including the “Do No Harm” principle and upholding human rights, underscore the importance of ethical conduct in addressing conflict. In conclusion, the paper asserts that the urgent need for research on global peace and harmony cannot be overstated. By advancing interdisciplinary research agendas, leveraging technology, strengthening international cooperation, and upholding ethical principles, humanity can collectively strive towards a more peaceful and harmonious world. Ultimately, it calls for courage, conviction, and unwavering commitment in the pursuit of a better world for all.